Gender in Global Studies - Horn, Laura (Kvinder, Køn & Forskning, 2017)
Gender constitutes a fundamental intersection of social power relations in processes of globalization. As such, it could be expected that gender should be a prominent focus in Global Studies which is concerned with issues of inequality and human progress. This article discusses how this engagement remains troubled in many regards and the possibilities for more focus on gender into Global Studies. Specifically, the article draws on the experience of teaching an intensive course on ‘Gendering Global Studies’ and discusses the pedagogy of teaching gender and the various challenges arising from this. Specific attention is given to the attempt to establish an inclusive learning environment; a balancing of a wide range of perspectives, particularly masculinities research and a strong conceptual focus on intersectionality; and a discussion of how a gender focus impacts on method and research practice. The article contributes to overall discussions about the nature of Global Studies; but more importantly it also seeks to highlight some of the ongoing challenges and opportunities in gender teaching in social sciences, and to offer concrete suggestions and pathways for bringing in a gender focus into Global Studies teaching.